Recovery of the PHA Copolymer P(HB-co-HHx) With Non-halogenated Solvents: Influences on Molecular Weight and HHx-Content - Bartels, Moritz; Gutschmann, Björn; Widmer, Torsten; Grimm, Thomas; Neubauer, Peter; Riedel, Sebastian L. (Frontiers in Bioengineering and Biotechnology, 2020)
Biodegradable and biocompatible polyhydroxyalkanoates (PHAs) are promising alternatives to conventional plastics. Based on the chain length of their monomers they are classified as short chain length (scl-) or medium chain length (mcl-) PHA polymers. The type of monomers, the composition and the molecular weight (MW) define the polymer properties. To accelerate the use of PHA as a bulk material, the downstream associated costs need to be minimized. This study focuses on the evaluation of non-halogenated solvents, especially acetone as a scl-PHA non-solvent, for the recovery of poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) – P(HB-co-HHx) – with an mcl-HHx content >15 mol% and a MW average (Mw) < 2∙105 Da. Solvents and precipitants were chosen regarding zeotrope formation, boiling point differences, and toxicity. Non-halogenated solvent-precipitant pairs were evaluated regarding the MW characteristics (MWCs) of the extracted polymer. Acetone and 2-propanol as a low toxic and zeotropic solvent-precipitant pair was evaluated at different extraction temperatures and multiple extraction times. The extraction process was further evaluated by using impure acetone for the extraction and implementing a multi-stage extraction process. Additionally, P(HB-co-HHx) extracted with three different solvents was characterized by 1H and 13C-APT NMR. The screening of precipitants resulted in a negative influence on the MWCs by ethanol precipitation for extractions with acetone and ethyl acetate, respectively. It was observed, that extractions with acetone at 70°C extracted a higher fraction of PHA from the cells compared to extractions at RT, but the Mw was decreased by 9% in average. Acetone with a 2-propanol fraction of up to 30% was still able to extract the polymer 95% as efficient as pure acetone. Additionally, when acetone and ethyl acetate were used in a multi stage extraction process, a two-stage process was sufficient to extract 98 – 99% of the polymer from the cells. 1H and 13C-APT NMR analysis confirmed the monomer fraction and structure of the extracted polymers and revealed a random block copolymer structure (D < 0.2). The presented strategy can be further developed to an ecological and economically feasible PHA downstream process and thus contributing to the commercialization of low cost PHAs.